Wind power potential and characteristic analysis of Chiang Mai, Thailand - Tanate Chaichana (2018)
An investigation of wind characteristics and wind energy potential at Chiang Mai Province, Thailand was studied. Wind data taken from the weather station at Chiang Mai International Airport between 2001-2006 was analyzed in order to obtain the potential energy generated by a Vertical Axis Wind Turbine (VAWT). It was found that the yearly average wind velocity was 5.7 meters per second with a standard deviation value of 2.2 meters per second. The analysis assumed that wind blew in the S. W. to N. E. direction. Two parameters for the local wind, the shape parameter (k) and scale parameter (c) were obtained at 2.928 and 6.381 meters per second, respectively. The estimated power that could be generated by a Vertical Axis Wind Turbine was 183.09 W/m2at 30 meters above ground level. This particular site corresponds to class 1 wind power. This level of power density may be adequate for non-connected electrical and mechanical applications, such as battery charging and water pumping. © 2010 The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg.